ZEOLITE PROCESSING TECHNOLOGY TO BECOME MATERIAL WITH HIGH ECONOMICAL VALUE - Didiek Hadjar Goenadi (Jurnal Zeolit Indonesia, 2004)
Zeolite is a group of hydrated silical alumino mineral from alkaline specially sodium (Na), Potassium (K), Calcium (Ca), and Magnesium (Mg). More then 2000 years since it found the first time by Cronstedt on the year 1756 in Sweden have been found more then 50 type of natural zeolite and 150 type synthetic zeolite. The use of zeolite covers a wide range of field due to its ability as absorber, catalyst and ion exchange. However, the use of natural zeolite have several limitation such as limited source, a very high variation mineral composition, and crystal size, porosity and un uniform pore diameter. On the other hand, synthetic zeolite is created to overcome the difficulty and weaknesses of natural zeolite. Several technological research and development have been carried out to increases the economic value of zeolite by exploitation and modifying zeolite capacity as absorber, catalyst and ion exchanger. Zeolite have been used on agriculture, cosmetics, and other industries.